Unconventional Allies Reunited: Liberal Hawks and Neoconservatives at the Turn of the Century - Just, Peter (Current Objectives of Postgraduate American Studies, 2012)
The paper argues that liberal hawks and neoconservatives formed an at first glance unconventional alliance during several international conflicts after the end of the Cold War. An analysis of the respective histories of the two schools of thought shows though that the cooperation is actually rooted in common origins and various similarities in their ideologies.